HOW TO TEACH VOCABULARY TO YOUNG LEARNERS (1-5 CLASSES) - Baratova Sevara Furqatovna; Jo’rayeva Sevinch Komil qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Vocabulary learning plays a crucial role in overall language development of young learners. Children with a broad vocabulary knowledge have higher academic achievement in all subject areas, including reading, writing, and math. In this article, we will discuss several effective methods and strategies for teaching vocabulary to young learners in grades 1-5. These methods and strategies include providing contextualized input, using visual aids, playing games.